Let $\alpha(s)$ be a regular and biregular curve in $\mathbb{R}^3$ parametrized in arc length with its curvature $k(s)$ and torsion $\tau(s)$. Then we can think of it's tangent vector $T(s)$ as another curve which range is contained on the unit sphere, let's call it $\beta(s)=\alpha'(s)$ with its curvature, say $k_1(s)$. I have to prove the following relation:

$$k_1^2=\frac {k^2+\tau^2}{k^2}$$

I've tried different approaches and I've derived some relations (maybe true as long as my calculation were right) using Frenet-Serres formula but I still cannot conclude.


Since the following discussion addresses multiple curves $\gamma$ each which its own tangent, normal, and binormal vectors, I will distinguish 'twixt the Frenet-Serret apparatus of different curves via subscripting: thus the unit tangent vector to $\gamma$ will be denoted by $T_\gamma$ and so forth.

We are considering the curve $\beta(s)$ given as the tangent vector $T_\alpha(s)$ to the unit speed curve $\alpha(s)$, so that

$\beta(s) = T_\alpha(s) = \alpha'(s) \tag 1$


$\langle \beta(s), \beta(s) \rangle = \langle T_\alpha(s), T_\alpha(s) \rangle = 1, \tag 2$

and we wish to compute the curvature $\kappa_1(s)$ of $\beta(s)$. One way of addressing this is to express the Frenet-Serret apparatus of $\beta(s)$ in terms of $\alpha(s)$ and its Frenet frame $T_\alpha$, $N_\alpha$, $B_\alpha$. We recall that $s$ is the arc-length along $\alpha(s)$; however, $s$ is not in general the arc-length along $\beta(s) = T_\alpha(s)$; that is, $\beta(s)$ is not in general a unit-speed curve. We thus donote the arc-length along $\beta$ by $\sigma$; then $T_\beta$ is given by

$T_\beta(\sigma) = \beta'(\sigma) = \dfrac{dT_\alpha(s)}{ds}\dfrac{ds}{d\sigma} = \kappa(s)N_\alpha(s)\dfrac{ds}{d\sigma}, \tag 3$

and since

$\Vert T_\beta(\sigma) \Vert = \Vert N_\alpha(s) \Vert = 1, \tag 4$

it follows from (3) that

$\left \vert \kappa(s) \dfrac{ds}{d\sigma} \right \vert = \left \vert \kappa(s) \dfrac{ds}{d\sigma} \right \vert \Vert N_\alpha(s) \Vert = \left \Vert \kappa(s) \dfrac{ds}{d\sigma} N_\alpha(s) \right \Vert = \Vert T_\beta(\sigma) \Vert = 1;\tag 5$

we conclude from (5) that

$\kappa^2(s) \left ( \dfrac{ds}{d\sigma} \right )^2 = \left \vert \kappa(s) \dfrac{ds}{d\sigma} \right \vert^2 = 1, \tag 6$

a formula which we shall shortly deploy. Since $\kappa(s) > 0$, we may also write

$\kappa(s) \left \vert \dfrac{ds}{d\sigma} \right \vert = \left \vert \kappa(s) \dfrac{ds}{d\sigma} \right \vert = 1, \tag 7$

and from this we see that

$\kappa(s) \dfrac{ds}{d\sigma} = \pm 1; \tag 8$

by reversing the direction of traverse of $\beta(\sigma)$ with respect to $s$ if necessary we may also assume that $ds / d\sigma > 0$, so that in fact

$\kappa(s) \dfrac{ds}{d\sigma} = 1, \tag 9$

which, though not further necessary here, is worth noting in it's own right.

We compute the curvature $\kappa_1(\sigma)$ of $\beta(\sigma)$ via the Frenet-Serret equations; as applied to $\beta(\sigma)$, we find via (3) that

$\kappa_1(\sigma) N_\beta(\sigma) = T_\beta'(\sigma) = \dfrac{d}{d\sigma} \left ( \kappa(s)N_\alpha(s)\dfrac{ds}{d\sigma} \right ); \tag{10}$


$\dfrac{d}{d\sigma} \left ( \kappa(s)N_\alpha(s)\dfrac{ds}{d\sigma} \right ) = \dfrac{d}{d\sigma} \left ( \left (\kappa(s)\dfrac{ds}{d\sigma}\right )N_\alpha(s)\right )$ $= \dfrac{d}{d\sigma} \left (\kappa(s)\dfrac{ds}{d\sigma}\right ) N_\alpha(s) + \left ( \kappa(s)\dfrac{ds}{d\sigma}\right )\dfrac{d}{d\sigma} N_\alpha(s); \tag{11}$

from (8), we see that $(\kappa(s)ds / d\sigma)$ must be constant, whence

$\dfrac{d}{d\sigma} \left (\kappa(s)\dfrac{ds}{d\sigma}\right ) = 0; \tag{12}$

combining (8), (10), (11) and (12):

$\kappa_1(\sigma) N_\beta(\sigma) =\pm \dfrac{d}{d\sigma} N_\alpha(s); \tag{13}$

we proceed:

$\dfrac{dN_\alpha(s)}{d\sigma} = \dfrac{dN_\alpha(s)}{ds} \dfrac{ds}{d\sigma} = \dfrac{ds}{d\sigma} (-\kappa(s) T_\alpha(s) + \tau(s) B_\alpha(s)), \tag{14}$

by virtue of the Frenet-Serret equations for $\alpha(s)$; from (13) and(14),

$\kappa_1^2(\sigma) = (\kappa_1(\sigma) N_\beta(\sigma)) \cdot (\kappa_1(\sigma) N_\beta(\sigma)) = \left (\dfrac{d}{d\sigma} N_\alpha(s) \right) \cdot \left (\dfrac{d}{d\sigma} N_\alpha(s) \right)$ $= \left (\dfrac{ds}{d\sigma} \right )^2 (-\kappa(s) T_\alpha(s) + \tau(s) B_\alpha(s)) \cdot (-\kappa(s) T_\alpha(s) + \tau(s) B_\alpha(s))$ $= \left (\dfrac{ds}{d\sigma} \right )^2 (\kappa^2(s) + \tau^2(s)), \tag{15}$

where we have used $\Vert B_\alpha(s) \Vert = 1$, $T_\alpha(s) \cdot B_\alpha(s) = 0$ as well as (2) in this derivation. Finally, via (6),

$\kappa_1^2(\sigma) = \dfrac{\kappa^2(s) + \tau^2(s)}{\kappa^2(s)}, \tag{16}$

the desired result.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.